Landscape hemerobics in wetlands in the urban area of Inhumas, GO, Brazil (Terr@ Plural, 2021)
Wetlands are fragile ecosystems and are important for water recharge in rural and urban landscapes. However, urban occupation patterns do not highlight the local importance of these environments in providing ecosystem services and do not prevent their degradation. A viable methodology for assessing the levels of anthropization is the calculation of hemerobic indices, which in turn are associated with the level of technological dependence of the landscape. The objective of this research is to evaluate the level of hemerobicity of landscapes in the urban core of Inhumas, metropolitan region of the state of Goiás. Five hemerobic levels of wetland landscape were identified, where High and Maximum hemerobic levels predominate, which compromises their ecosystem functions. Cartography based on the principles of Landscape Geoecology indicates hierarchical levels that can be considered by the public authorities in urban planning and management. This enables the selection of critical areas for mitigation, recovery and rehabilitation interventions in the urban environment.
Keywords: ecosystem services; Technological dependence on the landscape; Landscape geoecology